Receptivity of livestock farmers adjacent to wetland ecosystems in the establishment and management of integrated livestock farms - Vargas Sibaja, María Marcela (2017)
The main objective of this investigation was to study the receptivity, application and usefulness of small farmers in the framework of the project Establishment and Management of Integrated Farms. The project started in 2014 and finished in December 2016; it was conducted in the ecosystem of Mata Redonda wetland, Rosario de Nicoya, Costa Rica.The project was born thanks to the results of the relation between the sustainable agricultural production and the conservation of wetlands, which were identified in the execution of the Plan General de Manejo Refugio Nacional de Vida Silvestre Mata Redonda (General Plan for Management of Mata Redonda National Wildlife Refuge) by the Centro Mesoamericano de Desarrollo Sostenible del Trópico Seco (Mesoamerican Center for Sustainable Development of the Dry Tropics- CEMEDE) in 2013. This paper analyzes the interest expressed by the community during the implementation of the project. It also analyzes the farmers’ experience when implementing alternative, sustainable, agricultural technologies as measures for adaptation to the climate change in their farms, as well as the difficulties and achievements these producers faced. The project consisted of a participatory work between the academy, the community and the administration of the Área de Conservación Tempisque (ACT-Tempisque Conservation Area), which promoted the implementation of sustainable technologies for the conservation of the wetland ecosystems.